2017
DOI: 10.1080/15476286.2017.1325067
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA-338 modulates cortical neuronal placement and polarity

Abstract: The precise spatial and temporal regulation of gene expression orchestrates the many intricate processes during brain development. In the present study we examined the role of the brain-enriched microRNA-338 (miR-338) during mouse cortical development. Reduction of miR-338 levels in the developing mouse cortex, using a sequence-specific miR-sponge, resulted in a loss of neuronal polarity in the cortical plate and significantly reduced the number of neurons within this cortical layer. Conversely, miR-338 overex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 47 publications
0
8
0
Order By: Relevance
“…Inhibition of miR-26a led to a decrease in neurons with single axonal projections, while its overexpression promoted the generation of neurons with multiple 'axon-like' neurites. In a recent study, miR-338 was shown to have a role in neuronal placement and polarisation in the cortical plate, controlling neuronal polarity, migration and/or cortical placement cues (Kos et al, 2017a). In the case of miR-26a, we show a cellautonomous role in the regulation of axon specification and growth of CNS neurons, a function that was also recently described for miR-140-3p (Ambrozkiewicz et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Inhibition of miR-26a led to a decrease in neurons with single axonal projections, while its overexpression promoted the generation of neurons with multiple 'axon-like' neurites. In a recent study, miR-338 was shown to have a role in neuronal placement and polarisation in the cortical plate, controlling neuronal polarity, migration and/or cortical placement cues (Kos et al, 2017a). In the case of miR-26a, we show a cellautonomous role in the regulation of axon specification and growth of CNS neurons, a function that was also recently described for miR-140-3p (Ambrozkiewicz et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…Despite this growing number of studies demonstrating the importance of miRNAs in axon and synapse development (Rajman and Schratt, 2017;Swanger and Bassell, 2011), evidence for their role in axon specification and neuronal polarisation has been largely missing. Only recently, miR-338, which was previously reported to control axonal outgrowth in cortical and superior cervical ganglion neurons (Aschrafi et al, 2008;Kos et al, 2017b), was shown to modulate cortical neuron migration and to have an effect in neuronal morphology and polarity in vivo (Kos et al, 2017a). Furthermore, a recent paper by Ambrozkiewicz et al (2018) demonstrated the capacity of miR-140 to act synergistically with its host gene E3 ubiquitin ligase WW-containing protein 2 (Wwp2) and Wwp1 in the establishment of axon-dendrite polarity of developing cortical neurons in vivo.…”
Section: Introductionmentioning
confidence: 99%
“…Although no obvious decline was observed in the expression of miR-338-5p in 10-month-old WT mice, the decline of miR-338-5p in APP/PS1 mice was accelerated, and the underlying mechanisms remains to be elucidated. The reason may be that the decreased expression of miR-338-5p was related to neuron integrity [ 18 ]. The concentration of miR-338-5p in serum has been raised as a potential diagnostic biomarker in colorectal cancer [ 39 ] and retinoblastoma [ 40 ].…”
Section: Discussionmentioning
confidence: 99%
“…As shown by the previous studies, selective overexpression or inhibition of miR-338 in cortical neuron improved or damaged the dendritic complexity and axon outgrowth [ 19 ]. Additionally, silencing miR-338-5p led to the loss of neuronal polarity and significantly decreased the number of neurons [ 18 ]. Nevertheless, it’s reported that the decreased expression of miR-338-3p correlates with neuronal survival [ 41 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation